KELAYAKAN MODUL MATAKULIAH BERBICARA DIALEGTIK (Penelitian Pengembangan Mahasiswa Prodi. Pend. Bahasa dan Sastra IndonesiaUNPARI) - Jamaludin, Jamludin; Nugroho, Agung; Grinitha, Virry; Kurniawan, Huda (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
This study aims to describe the feasibility of a valid and practical dialectical speaking module for students of the Indonesian Language and Literature Education Study Program STKIP PGRI Lubuklinggau. The method used is Research and Development (R&D) research and the Dick & Carey model is limited to 8 stages. a) analysis of needs and objectives; b) learning analysis; c) analysis of learning (students) and context; d) formulating performance objectives; e) developing instruments; f) developing learning strategies; g) developing and selecting learning materials; h) designing and conducting formative evaluations; i) make revisions; j) summative evaluation but in this study it is limited to the formative evaluation stage. The results of the research and the calculation of the questionnaire from the Dialectical Speaking module design experts were categorized as very good with a percentage of 87.5%, linguistic validation 85%, in the very good category, and material validation at 90.91% in the very good category. The overall result of the validation is 86.96%, based on this percentage range, the online-based Dialectical Speaking module is valid and practical. Research that produces a new product in the form of a dialectical speaking module and is tested for validity and practicality.